Идентификация неопознанных порохов и взрывчатых веществ, остатков взрыва и выстрела - Межевич, Г. В.; Буллер, М. Ф.; Ярманова, С. П. (НТУ "ХПИ", 2007)
The possibility of identification of unidentified powders and explosives with aid of different methods of analytic chemistry has been examinated. The characteristics of components of powders and explosives required for identification have been given. It has been obtained the chromatographic characteristics of components of powders and explosives, allowed to carry out the identification by method of fine layer chromatography. The example of identification of unidentified explosive has been given.
Keywords: остатки выстрела; остатки взрыва; идентификация пороха